Toxic Epidermal Necrolysis : A Case Report in 9-Year Old Girl - Nurwestu Rusetiyanti; RR. Vetria Sekar Damayanti; Ravicka Rakhmayunita; Sugiarsih Sugiarsih (Academic Hospital Journal, 2018)
Introduction. Toxic Epidermal Necrolysis (TEN) is a acute and severe reactions of skin and mucosa that can lead to serious clinical outcomes and morbidity. TEN is considered to be rare in children and usually has a fatal outcome due to sepsis.Case. 9-year old girl, went to Universitas Gadjah Mada (UGM) Hospital with complaint of erythematous, purpuric rash, blister starting from the neck and also involving the inside of the mouth, lips and eyes, and spreading over the entire body. Three weeks before hospital admission, she received combination of drugs valproate sodium, clonazepam, phenobarbital and piracetam. Two week after, she developed skin rash and progress to develop TEN. Sodium valproate and clonazepam were discontinued, and intravenous methylprednisolone, prophylactic systemic antibiotics, intravenous immunoglobulin (IVIG), intravenous fluid supplement, antipyretic, special wound care at semi sterile room, and supportive medical care fro TEN were administered. She was discharged from hospital in a stable, good condition.Discussion. This case suggests that sodium valproate contributed to the development of TEN. Appropriate case management will give excellent result, and reduce long-term complications.